Fly Swatter Game Effect on Seventh Grade Students’ Vocabulary at SMP Parulian 2 Medan - Safna, Nur Anjelina; Tampubolon, Sahlan; Lumbantobing , Febrina S.L.; Wafa, Ali (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2025)
This research examines the impact of the Fly Swatter Game on seventh-grade students' vocabulary proficiency at SMP Parulian 2 Medan. The research employed a true experimental design, categorising students into an experimental group that participated in the Fly Swatter Game intervention and a control group that received traditional instruction. Both groups took pre-tests and post-tests to assess their vocabulary enhancement. The study's findings indicated that the experimental group demonstrated a significant enhancement in vocabulary knowledge compared to the control group. The average score of the experimental group increased from 58.26 (pre-test) to 77.33 (post-test). The t-test analysis resulted in a t-count of ( 3.144,) which was higher than at the level of significance= 0,05 (1,673) or > 3,144 > 1,673. Ha was accepted, whereas Ho was refused. demonstrating a statistically meaningful impact. The findings indicate that employing the Fly Swatter Game as a vocabulary instruction technique can improve students' engagement, motivation, and retention of new lexicon. The game-based learning methodology enables students to engage actively with vocabulary, enhancing both enjoyment and efficacy in the learning process